(3TQM OhGhjf GdTYQGA GdSJIs - (3eLghds
(3ChdgG (B:s
(3Chd GdehLhO efg baG fHc ef PcQi MHjH hefRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3ChQOJgG hUOhQ GdYjf eSHbI hGdUHM HGdchcH GdPi efehQ ced LejY TYQ YdbI HMeO Gddg JYGdi ced GdSaQ GdChd s
(3GdfSNI HgG MhGTs
(3JMJhi OhGhjf GeQF GdbjS hGdfGHZI GdPHjGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs